Batasan Perjanjian Perkawinan yang tidak Melanggar Hukum, Agama, dan Kesusilaan - Nurdiyanawati, Lisa Wage; Hamidah, Siti (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2019)
This study aims to describe the marriage agreement based on legal norms, morality norms and religious norms prevailing in the Indonesian society. This normative research produces three conclusions. First, marriage agreements that do not violate the law are agreements that fulfill the legal requirements under the Civil Code and the provisions of Law Number 1 Year 1974. Second, marriage agreements that do not violate religion are agreements whose substance does not conflict with Islamic law. Third, a marriage agreement that does not violate morality is a marriage agreement that does not violate the norms of decency in general or customary law that applies to society.